Maize (Zea mays) genotypes for intercropping with cassava (Manihot esculenta) in southern Nigeria; 2: growth morphological changes and yield advantages - Ezumah, H.C.; Arthur, J.; Osiru, D.; Fajemisin, J. (1990)
Five maize genotypes differing in plant habit and growth period were evaluated at 5 population densities (10, 20, 40, 80 and 160 × 103 plants/ha) under an intercropping system with cassava cv. TMS30572 at 1 × 1 or 1 × 0.67 m spacing in a tropical Alfisol in southern Nigeria. Increasing the maize population enhanced cassava height and internode length but decreased leaves and branches/plant and stem diameter, and hence yield. The effects on maize plants of increasing the maize population were increased ear insertion and plant heights, days to 50% tasselling, and root and stem lodging and decreased leaf angle and stem diameter. The effects of high maize populations on cassava traits persisted for 7 months, even though the maize was harvested 3 months after cassava planting. Cassava stem girth was significantly affected by maize genotype. Land equivalent ratios indicated that early maturing, short maize varieties produced the best cassava and maize yields at 80 000 plants/ha while late maturing, tall varieties were best at 40 000 plants/ha.